INTERNATIONALIZATION OF COLOMBIAN STARTUPS NEW RESEARCH INSIGHTS - Juan Sebastián Betancourt Chaparro; Tilman Jundt (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2021)
The objective of this paper is to complement the material about the Colombian entrepreneurial landscape. Primary data was collected and analyzed through an online perception survey to better understand the dynamics of internationalization. This study offers a holistic insight into the internationalization of Colombian startups by comparing their behavior and patterns with the internationalization of Colombian Multilatinas. The study shows how Colombian startups could follow the path of Chilean Born Globals by presenting their most decisive factors of success and how Colombian startups are standing compared to them. Results are compared with previous research on Colombian Multilatinas, (Gonzalez-Perez, M. A., & Velez-Ocampo, J. F., 2014) and show that development level of the target market is the second important aspect to factors which play equally to multinational. In contrast to MNE, cultural proximity seems to have a higher impact on internationalization decisions of entrepreneurs.